Annual changes of Neohelice granulata cognitive abilities indicate opposition between short- and long-term memory retention - Anahi, Rosso (2023)
Neohelice is a long-standing model for memory studies for its strong retention of a reduced escape response when trained to iterative presentations of a visual danger stimulus (VDS). Here we present year-round changes that are related to the memory acquisition, storage, and expression. First, we evaluated exploratory activity and response to the VDS, as necessary for memory acquisition and expression. Both parameters change year-round. Second, short-term memory (STM) and two types of long-term memory (LTM) were assessed throughout the year. STM and long-term context-dependent signal memory (CSM) change between periods of the year, whereas signal memory (SM) does not, indicating that the cognitive abilities of the crab display circannual rhythms. Third, during the reproductive period, STM retention is higher than both CSM and SM, indicating a trade-off between STM and LTM. This is the first report of memory retention abilities changing seasonally as a trade-off between short- and long-term memories.